2009
DOI: 10.1523/jneurosci.1805-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3a Is Broadly Neuroprotective In Vitro and In Vivo against Insults Implicated in Motor Neuron Diseases

Abstract: Aging is a risk factor for the development of adult-onset neurodegenerative diseases. Although some of the molecular pathways regulating longevity and stress resistance in lower organisms are defined (i.e., those activating the transcriptional regulators DAF-16 and HSF-1 in Caenorhabditis elegans), their relevance to mammals and disease susceptibility are unknown. We studied the signaling controlled by the mammalian homolog of DAF-16, FOXO3a, in model systems of motor neuron disease. Neuron death elicited in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 69 publications
5
82
1
1
Order By: Relevance
“…In this report, we confirm that mitochondria from cells expressing mSOD1 have impaired ATP production, and this is associated with activation of the energy sensor AMPK. This observation is consistent with previous literature reporting dysregulation of various metabolic genes in mSOD1 models, including fatty acid synthase, fatty acid transporter (FAT/CD36), glucose transporter 4, p53, FOX03A, mTOR, and nitric oxide synthase, all of which are downstream targets of the AMPK pathway (Gonzalez de Aguilar et al, 2000;Martin, 2000;Lukas et al, 2006;Fergani et al, 2007;Lobsiger et al, 2007;Morimoto et al, 2007;Gonzalez de Aguilar et al, 2008;Martinez et al, 2008;Mojsilovic-Petrovic et al, 2009) (Lim and Kalb, unpublished observations). Furthermore, we show that AMPK activation has adverse effects on genetic models of motor neuron disease.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this report, we confirm that mitochondria from cells expressing mSOD1 have impaired ATP production, and this is associated with activation of the energy sensor AMPK. This observation is consistent with previous literature reporting dysregulation of various metabolic genes in mSOD1 models, including fatty acid synthase, fatty acid transporter (FAT/CD36), glucose transporter 4, p53, FOX03A, mTOR, and nitric oxide synthase, all of which are downstream targets of the AMPK pathway (Gonzalez de Aguilar et al, 2000;Martin, 2000;Lukas et al, 2006;Fergani et al, 2007;Lobsiger et al, 2007;Morimoto et al, 2007;Gonzalez de Aguilar et al, 2008;Martinez et al, 2008;Mojsilovic-Petrovic et al, 2009) (Lim and Kalb, unpublished observations). Furthermore, we show that AMPK activation has adverse effects on genetic models of motor neuron disease.…”
Section: Discussionsupporting
confidence: 93%
“…When more than one recombinant HSV vector was used, 1.5 l of each viral stock was added, yielding a total of 3 l of viral stocks to 1 ml of media. Previous work has shown that both transgenes are expressed in Ͼ95% of neurons in a nontoxic manner under these circumstances (Mojsilovic-Petrovic et al, 2009). To quantify motor neurons, immunostained cells were counted in four to five randomly selected fields in each coverslip.…”
Section: Reverse-transcribed Pcr and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Dissociated spinal cord cultures from wild-type mice were differentiated for 3 weeks and then infected with AAV to express full-length human AR (AR24Q or AR111Q) tagged with a C-terminal FLAG epitope. As previously shown for motor neurons expressing untagged polyglutamine-expanded AR (27,29,30), a substantial number of motor neurons died by 8 days of treatment with DHT (Fig. 2D, right panel).…”
Section: Intranuclear Inclusions In Sbma Cell Models Contain Fulllengsupporting
confidence: 81%
“…Primary Dissociated Spinal Cord Cultures and AAV Infection-Dissociated spinal cord cultures were established according to Roy et al (28) with modifications as described (11,29,30). Briefly, spinal cords from non-transgenic 13.5-day-old mouse embryos were dissected on ice in dissection medium (0.1% dextrose, 2% sucrose, 6.8 mM NaCl, 0.27 mM KCl, 8.4 M Na 2 HPO 4 , 11 M KH 2 PO 4 , and 9.9 mM HEPES), pooled, dissociated with trypsin, plated on poly-D-lysine (Sigma)-coated German glass coverslips (Chemglass Life Sciences), and cultured for 3 weeks in glial conditioned medium (minimum essential medium, 3% charcoal-stripped horse serum, 35 mM NaHCO 3 , 0.5% dextrose, 1% N3, 10 nM 2.5S nerve growth factor).…”
Section: Construction Of Double Labeled Expanded Polyglutamine Ar (Dmentioning
confidence: 99%
“…Similarly, activation of FOXO in mammalian neurons induced cell death (Gilley, Coffer & Ham, 2003; Yuan et al., 2008, 2009). By contrast, constitutively active FOXO protected neurons against excitotoxic and proteotoxic insults (Mojsilovic‐Petrovic et al., 2009). …”
Section: Introductionmentioning
confidence: 99%